2016
DOI: 10.1080/08820538.2016.1238095
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Endophthalmitis in children: Epidemiology, Diagnosis, Management, and Prognosis

Abstract: Pediatric posttraumatic endophthalmitis presents with great complexities and challenges arising due to delayed presentation, difficulty in eliciting an accurate history, or trauma with unusual and highly contaminated objects. The possibility of initial misdiagnosis as panuveitis, metastatic endophthalmitis, and masquerade syndrome is also very high, which results not only in several unwarranted investigations being performed, but also a delay in the initiation of treatment. The standard treatment remains prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 70 publications
0
24
0
1
Order By: Relevance
“…Among patients with streptococcal endophthalmitis, Streptococcus pneumoniae , viridans group streptococcus and group B β-haemolytic streptococcus were the main isolates, although the dominant isolates varied in different studies [ 8 11 ]. Previous studies have focused on paediatric post-traumatic endophthalmitis caused by all pathogens [ 12 14 ]. They found that the streptococcus species was a common cause of post-traumatic endophthalmitis in children.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with streptococcal endophthalmitis, Streptococcus pneumoniae , viridans group streptococcus and group B β-haemolytic streptococcus were the main isolates, although the dominant isolates varied in different studies [ 8 11 ]. Previous studies have focused on paediatric post-traumatic endophthalmitis caused by all pathogens [ 12 14 ]. They found that the streptococcus species was a common cause of post-traumatic endophthalmitis in children.…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic endophthalmitis (PTE) is considered as one of the most serious complications after OGIs, and the incidence of this disease varies from 3.6%–54.16% in different studies [6,7]. Although advanced antibiotics and treatment techniques currently exist, children diagnosed with PTE were generally reported to have a poor outcome [8]. Some risk factors were reported to be associated with the development of PTE, such as the delayed timing of primary repair, a large wound size, a retained intraocular foreign body, the location of the wound, a rural location, the female gender, and an age greater than 50 years old [9].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma is the most common cause of endophthalmitis in children with incidence reported between 2% and 70%[ 1 2 ] most commonly due to Streptococci and Staphyloccal species. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%